A race between two races: positioning and power demands during cycling in a sprint triathlon world championship - Nolte, S.; Quittmann, O. J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Drafting in short-distance triathlon cycling introduces variable power demands [1,2]. Performance evaluations solely based on cycling split times may overlook the differing power requirements experienced by riders even within the same bike group. Factors like positioning within the bike group could influence power demands and subsequently initial fatigue in the following run segment of a triathlon [3]. METHODS: We analyzed power data and television-based positional information from the 2020 male sprint triathlon World Championship event held in Hamburg. Specifically, we focused on five of the eight riders from the leading bike group, examining their power profiles and power distributions. Employing hierarchical Bayesian models, we analyzed the association between positioning within the group and the power demands during accelerations following turns. Our study was preregistered and has open data and code available. RESULTS: Within the same bike group, athletes showed distinct power profiles and employed different positioning strategies. Notably, as athletes positioned themselves further back during a turn, they demonstrated higher peak power (+24.2 W [4.8; 36.7] per position; mean [95% credibility interval]) and 10 seconds mean power (+19.3 W [10.5; 27.1]) during subsequent accelerations. However, the effect of positioning was less pronounced on the 20 seconds mean power (+6.3 W [-1.4; 13.6]), and it had a negative impact on the 20 seconds mean power before the turn (-13.4 W [-20.8; -4.99]). CONCLUSION: The positioning of athletes during cycling in a triathlon can impact the power demands, potentially influencing the performance during the subsequent running leg. Our findings indicate that to reduce power demands, athletes should position themselves at the front of the group during turns and towards the back for the remainder of the cycling segment. However, employing this strategy will likely compromise cooperative group work. Therefore, athletes and coaches must develop positioning strategies based on data and experience, tailored to individual abilities. Future studies should aim to correlate power variability with running performance in races, while accounting for individual running performance levels.